Romanian wine sector in the context of climate change - Livia Mirescu; Alexandra Cristina Ciotec (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Climate change is one of the major challenges of our century - a complex area in which to improve our knowledge and understanding to take immediate measures to effectively address and correct, in terms of the challenges of climate change, respecting precautionary principle. (Romanian National Strategy on Climate Change). In this paper we discussed the main issues facing the wine and measures to mitigate possible negative effects.
Keywords: 330; Viticulture; Climate changes; Agriculture; Food safety